IMPACT OF COLORS ON SOCIAL AND POLITICAL LIFE: रंगों का सामाजिक एवं राजनीतिक जीवन पर प्रभाव - Kumar Ojha, Narendra (International Journal of Research -GRANTHAALAYAH, 2014)
Colors have a close relationship with human life. Human life is incomplete without colors, colors have an impact on the socio-economic, political, life of human beings, there are many types of colors like yellow, red, green, purple, blue, black, white etc. Each type has its own color It has special significance and has its own unique identity, such as red color is stimulating and attractive, it is very active and aggressive, it manifests anger, courage, valor, beauty, it is very popular among women, Women prefer to wear red colored saris at the time of worship of God on festivals, even red is the most preferred color for the clothes of God. The red color is also closely related to politics, even the identity of the communist party of India, the Communist Party of Marxist and the Communist Party is from the red flag, "Red salute of comrades". The blood which is the basis of human body is also red. The red color is also a symbol of danger, the traffic signal is red colored due to which the entire traffic stops. Hence, red color has its own unique identity. It is unfortunate that today terrorists are playing blood red Holi in the whole world, it is a dangerous sign for the whole of humanity. This terrorism has to be stopped, it will have to be seen what color of international political will be able to stop this dreaded canker. We are waiting for that day. रंगों का मानवीय जीवन के साथ निकट का सम्बन्ध है। रंगों के बिना मानवीय जीवन अधुरा है, रंगों का मानव के सामाजिक आर्थिक, राजनीतिक, जीवन पर प्रभाव पड़ता है, रंग कई प्रकार के होते है जैसे पीला, लाल, हरा, बैंगनी, नीला, काला, श्वेत आदि हर प्रकार के रंग का अपना विशिष्ट महत्व है और इसकी अपनी विशिष्ट पहचान है, जैसे लाल रंग उत्तेजक एवं आकर्षक होता है, यह अत्यन्त ही सक्रिय एवं आक्रामक होता है, इसके द्वारा क्रोध, साहस, वीरता, श्रृंगारिकता प्रकट होती है, महिलाओं में यह अत्यंत ही लोकप्रिय होता है, महिलायें त्यौहारों पर ईश्वर की आराधना के समय लाल रंग की साड़ियाॅं पहनना ही ज्यादा पसंद करती है यहाॅं तक कि भगवान के वस्त्रों के लिए भी लाल रंग का चयन सर्वाधिक होता है। लाल रंग का राजनीति के साथ भी निकट का संबंध है, यहाॅ तक कि भारत के साम्यवादी दल, माक्र्सवादी कम्युनिस्ट पार्टी एवं कम्युनिस्ट पार्टी की पहचान ही लाल रंग के झण्डे से है, ’’कामरेड का लाल सलाम’’। खून जो मनुष्य के शरीर का आधार है, वह भी लाल ही है। लाल रंग खतरे का भी प्रतीक है, ट्राफिक सिग्नल लालरंग जिसके कारण सम्पूर्ण यातायात रूक जाता है। अतः लाल रंग की अपनी विशिष्ट पहचान है। दुर्भाग्य है कि आज सम्पूर्ण विश्व में आतंकवादी खून की लाल होली खेल रहे है, यह सम्पूर्ण मानवता के लिए एक खतरनाक संकेत है। इस आतंकवाद को रोकना होगा, देखना यह होगा कि अन्तर्राष्ट्रीय राजनीतिक का कौन सा रंग इस आतंकवाद खतरनाक नासूर को रोकने में कामयाब होगा उस दिन की हमें प्रतीक्षा है।